Child Social Welfare Institution Participation in the Implementation of Good Governance - Muhammad Rais Rahmat Razak; Akhwan Ali (Program Pascasarjana Universitas Negeri Makassar, 2019)
The application of the principles of good governance is not only limited to ministries and government agencies or central and regional government levels. The application of good governance needs to be extended to non-governmental social institutions such as children's social welfare institutions. Sejati Orphanage of Muhammadiyah Rappang is one of the social welfare institutions of children in South Sulawesi, founded by H. ismail Ambo Mariama since 1950 as a form of social concern for the massacre known as the 40,000 victims in December 1949 in South Sulawesi. This research aims to determine the level of participation and application of the principles of good governance in the orphanage. This research uses quantitative descriptive method by describing the two variables using the Likert scale and examining the relationship between the two variables using linear regression analysis. Samples is 30 was taken from 150 populations. The results show that the level of participation and application of the principles of good governance are included in the excellent category. While the level of participation influences 42.2 percent of the application of the principles of good governance. This shows that the application of the principles of good governance in social institutions is easier compared to other institutions.